Emotional and psychological experiences of nursing students caring for dying patients: an explorative study at a national referral hospital in Uganda - Asha K. Nabirye; Ian G. Munabi; Aloysius G. Mubuuke; Sarah Kiguli (BMC Medical Education)
Abstract Background Caring for dying patients is associated with psychological trauma, strong emotions and enormous stress for nursing staff and nursing students who are reliable health care providers in such difficult situations. Nursing students involved in End-of –life care need to work through these emotions during clinical placements. This study explored the lived experiences of nursing students caring for the dying patients at Mulago national referral hospital. Methods An explorative study was conducted using in-depth interviews among fifteen 3rd and 4th year undergraduate nursing students of Makerere University college of Health sciences. Data was audio recorded, verbatim transcribed and thematically analyzed using Atlas. ti version 6 software. Findings Two themes emerged from students’ narratives of their emotional and psychological experiences while caring for dying patients; (1) Psychological and emotional reactions, (2) Coping mechanisms. The sub-themes under Psychological and emotional reactions were; feelings of anger, triggers of anxiety symptoms, triggers of sadness and guilt feelings. The sub themes under coping mechanisms were; peer to peer support through interacting with each other about the experiences, engagement in problem solving, distancing from patients, spirituality and engaging in personal stress reducing activities. Conclusion Nursing students experience various negative psychological and emotional reactions but devise different coping mechanisms to overcome them. There is need for development of clear guidelines on orientation of nursing students caring for dying patients, emphasis on building their emotional intelligence and more research on effectiveness of end of life educational interventions to mitigate the anticipated negative psychological and emotional reactions.